Some Slater's Type Inequalities for Convex Functions Defined on Linear Spaces and Applications - S. S. Dragomir (Abstract and Applied Analysis)
Some inequalities of the Slater type for convex functions defined on general linear spaces are given. Applications for norm inequalities and f-divergence measures are also provided.